Vascular Anatomy and Variations of the Anterior Abdominal Wall – Significance in Abdominal Surgery - Stoyan Kostov; Svetla Dineva; Yavor Kornovski; Stanislav Slavchev; Yonka Ivanova; Angel Yordanov (Prague Medical Report, 2023)
Detailed knowledge of the human anatomy is an integral part of every surgical procedure. The majority of surgery related complications are due to a failure to possess appropriate knowledge of human anatomy. However, surgeons pay less attention of the anatomy of the anterior abdominal wall. It is composed of nine abdominal layers, which are composed of fascias, muscles, nerves, and vessels. Many superficial and deep vessels and their anastomoses supply the anterior abdominal wall. Moreover, anatomical variations of these vessels are often presented. Intraoperative and postoperative complications associated with entry and closure of the anterior abdominal wall could compromise the best surgical procedure. Therefore, sound knowledge of the vascular anatomy of the anterior abdominal wall is fundamental and a prerequisite to having a favourable quality of patient care. The purpose of the present article is to describe and delineate the vascular anatomy and variations of the anterior abdominal wall and its application in abdominal surgery. Consequently, the most types of abdominal incisions and laparoscopic accesses will be discussed. Furthermore, the possibility of vessels injury related to different types of incisions and accesses will be outlined in detail. Morphological characteristics and distribution pattern of the vascular system of the anterior abdominal wall is illustrated by using figures either from open surgery, different types of imaging modalities or embalmed cadaveric dissections. Oblique skin incisions in the upper or lower abdomen such as McBurney, Chevron and Kocher are not the topic of the present article.